Phase-only encoding of wide-angle 3D computer generated hologram - Szawerdak, Artur; Kukołowicz, Rafał; Idicula, Moncy Sajeev; Chlipała, Maksymilian; Kozacki, Tomasz (Photonics Letters of Poland, 2025)
Wide-angle capability is essential for holographic near-eye displays. Most of these employ phase-only spatial light modulators, so CGH must be encoded as phase-only holograms (PoHs). Thus, this paper investigates three known encoding methods: double phase hologram (DPH), direct phase only hologram (D-PoH), and complex amplitude modulation (CAM). To determine the most optimal phased-encoding method, we evaluate them by field of view, image quality, and diffraction efficiency. It was found that CAM gives very low brightness and quality; thus, improvement of the CAM is proposed. Also, we conclude that D-PoH is the optimal method for the wide-angle case. Full Text: PDF References T. Zhan, K. Yin, J. Xiong, Z. He, S.T. Wu, "ugmented Reality and Virtual Reality Displays: Perspectives and Challenges", iScience 23(8), 101397 (2020). CrossRef T. Gu, C. Han, H. Qin, K. Sun, "Phase-only hologram optimization with adaptive constraint strategy for high-quality optical reconstruction", Opt. Express 32(25), 379 (2024). CrossRef S.J. Liu, L.F. Feng, S.J. Ji, H.N. Yan, K. Yang, P.P. Li, D. Wang, "Speckle noise suppression method in holographic display using optimized pixel processing", Opt. Laser Technol. 181, 111644 (2025). CrossRef J. Wu, K. Liu, X. Sui, L. Cao, "High-speed computer-generated holography using an autoencoder-based deep neural network", Opt. Lett. 46(12), 2908 (2021). CrossRef O. Mendoza-Yero, G. Mínguez-Vega, J. Lancis, "Encoding complex fields by using a phase-only optical element", Opt. Lett. 39(7), 1740 (2014). CrossRef Y. Qi, C. Chang, J. Xia, "Speckleless holographic display by complex modulation based on double-phase method", Opt. Express 24(26), 30368 (2016). CrossRef J. Martinez-Carranza, T. Kozacki, "High diffraction efficiency complex amplitude modulation technique by using antiwave functions", Opt. Lett. 49(18), 5115 (2024). CrossRef T. Kozacki, J. Martinez-Carranza, I. Gerej, R. Kukolowicz, M. Chlipala, M. Sajeev Idicula, "Frequency domain method for wide angle computer generated hologram", Opt. Laser Technol. 181, 111610 (2025). CrossRef T. Kozacki, J. Martinez-Carranza, M. Chlipala, R. Kukolowicz, M. Sajeev Idicula, Arxiv (i), 1-18 (2024). CrossRef